"Honeycomb" vs square and cubic models - Brimkov, Valentin E.; Barneva, Reneta P. (Elsevier, 2001)
In this paper we summarize some observations about the advantages of using hexagonal grids in raster graphics. We initiate a study of honeycomb graphics, whose 2D version is based on a hexagonal grid, while in its 3D counterpart the voxels are hexagonal prisms. We design an analytical honeycomb geometry of linear objects, which parallels similar developments already known in classical raster graphics [6]. We also demonstrate certain advantages of honeycomb graphics, in particular that it provides a better tunnel-free approximation to continuous objects. © 2001 Published by Elsevier Science B.V.
IWCIA 2001, 8th International workshop on Combinatorial Image Analysis --
Keywords: Algorithms; Approximation theory; Computational complexity; Computational geometry; Computer science; Set theory; Topology; Vectors; Hexagonal grids; Honeycomb geometry; Raster graphics; Tunnel-free approximation; Computer graphics